Effectiveness of Implementing the 2013 Curriculum at SDN 010 Sungai Kunjang: Efektivitas Penerapan Kurikulum 2013 di SDN 010 Sungai Kunjang - Nur Agus Salim; Gamar Al Haddar; Yunita Mayasari (Borneo Educational Journal (Borju), 2021)
This study aims to find out the effectiveness of the implementation ofcurriculum 2013 in SD Negeri 010 Sungai KunjangSamarinda. A qualitative approach was applied to answer the research problem. The researcher involved school principal, teachers and first, second, fourth and fifth grade students as the research subjects through snowball sampling. Meanwhile, the research object was the implementation of curriculum 2013. Methodology triangulation was applied to check the trustworthiness of data, by comparing results of interview, result of observation and result of questionnaire. The data crosschecking was also conducted between sources, such as the school principal and the teachers, aboutthe implementation of curriculum 2013 in the research setting. Based on the data analysis, it is found that 1) the teachers havedocuments of lesson planning such syllabus and lesson plans which made independently through class KKG; 2) the teachers had implemented the learning process very well as it had been planned. However, some teachers have not had skill in information and technology so that they have difficulties in inputting data for students’ progress report; 3) the number of book for curriculum 2013 and the number of students are considered in adequate number; 4) the teachers had conducted the opening section, main section and closing section during the learning process; 5) the school principal had supervised the class at the beginning of the learning process.